Effect of Lycopene Against Cisplatin-Induced Acute Renal Injury in Rats: Organic Anion and Cation Transporters Evaluation - Erman, Fazilet; Tuzcu, Mehmet; Orhan, Cemal; Şahin, Nurhan; Şahin, Kazım (Humana Press Inc, 2014)
In the present study, we investigated the effects of lycopene on the expression of organic anion transporters (OATs), organic cation transporters (OCTs), and multidrug resistance-associated proteins (MRPs) of cisplatin-induced nephrotoxicity in rats. Twenty-eight 8-week-old Wistar rats were divided into four groups: control, lycopene-treated (6 mg/kg BW by oral gavage), cisplatin-treated (7 mg/kg BW, IP), and lycopene in combination with cisplatin-treated groups. In the presence of cisplatin, serum urea nitrogen (urea-N) (48.5 vs. 124.3 mg/dl) and creatinine (0.29 vs. 1.37 mg/dl) levels and the kidney efflux transporters MRP2 and MRP4 levels were significantly increased, whereas OAT1, OAT3, OCT1, and OCT2 levels in kidney were decreased in the treated rats compared with normal control rats. However, administration of lycopene in combination with cisplatin resulted in a reduction in the serum urea-N (124.3 vs. 62.4) and creatinine (1.37 vs. 0.40) levels and the kidney efflux transporters MRP2 and MRP4 proteins in the kidneys. Administration of lycopene to acute renal injury-induced rats largely upregulated the organic anion transporters (OAT1 and 3) and organic cation transporters (OCT1 and 2) to decrease the side effects of cisplatin. The present study suggests that lycopene synergizes with its nephroprotective effect against cisplatin-induced acute kidney injury in rats.
Keywords: Cisplatin; OATs/OCTs; MRPs; Kidney; Lycopene